Single coronary artery originating from the right aortic sinus without a left anterior descending and circumflex artery in conventional swine - Lim, Kyung-Seob (Korean Association for Laboratory Animal Science, 2013)
Single coronary artery is a rare coronary artery anomaly. Very few previous reports of this anatomical malformation in swine have been found. A 22 kg Yorkshire X Landrace F1 crossbred castrated male swine was presented for enrollment in a coronary stent implantion study. Coronary angiography revealed a single coronary artery arising from the right aortic sinus. The right coronary artery and anomalous left coronary artery were implanted with novel coronary stents without any side effects.